2020
DOI: 10.1002/anie.201915731
|View full text |Cite
|
Sign up to set email alerts
|

Complex Carbocyclic Skeletons from Aryl Ketones through a Three‐Photon Cascade Reaction

Abstract: Starting from readily available 7‐substituted 1‐indanones, products with a tetracyclo[5.3.1.01,704,11]undec‐2‐ene skeleton were obtained upon irradiation at λ=350 nm (eight examples, 49–67 % yield). The assembly of the structurally complex carbon framework proceeds in a three‐photon process comprising an ortho photocycloaddition, a disrotatory [4π] photocyclization, and a di‐π‐methane rearrangement. The flat aromatic core of the starting material is converted into a functionalized polycyclic hydrocarbon with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 66 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…With 4 in hand, we focused on the key step of our synthetic strategy, the photochemical reaction cascade furnishing the protoilludane core. Previous experiments 11,12,14 had shown that the desired photochemical transformation proceeds efficiently in freshly distilled dry methanol as the solvent (0.1 mΜ) and with irradiation at  = 300 or 350 nm. We were pleased to detect reasonably good conversions of 4 after irradiation at  = 300 and 350 nm for two hours ( Table 1, entries 1 and 2, respectively).…”
Section: Homentioning
confidence: 99%
See 4 more Smart Citations
“…With 4 in hand, we focused on the key step of our synthetic strategy, the photochemical reaction cascade furnishing the protoilludane core. Previous experiments 11,12,14 had shown that the desired photochemical transformation proceeds efficiently in freshly distilled dry methanol as the solvent (0.1 mΜ) and with irradiation at  = 300 or 350 nm. We were pleased to detect reasonably good conversions of 4 after irradiation at  = 300 and 350 nm for two hours ( Table 1, entries 1 and 2, respectively).…”
Section: Homentioning
confidence: 99%
“…Our modified approach commenced with the synthesis of photosubstrate 4, which was easily accessible in three steps starting from p-methylanisole (see Supporting Information). 11,14 The idea was to resolve the putative reaction product by a subsequent enantioselective reduction, which required a steric distinction of the substituents at the carbonyl carbon atom. The introduction of the gem-dimethyl substitution at C-11 was therefore postponed to a later stage after the resolution had been performed.…”
Section: Homentioning
confidence: 99%
See 3 more Smart Citations